CCAFS Branding and acknowledgment guidelines - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This document outlines the correct use of the CCAFS name, colours and logo, as well as the correct way to acknowledge the program in research outputs. The original branding and acknowledgment guidelines were published in 2013. CCAFS regularly updates the guidelines. The most recent version was published in September 2020.